Pengaruh Infrastruktur Jalan, Air Dan Listrik Terhadap Produk Domestik Regional Bruto Di Kota Kupang (Jurnal Ekonomi Pembangunan Widya Mandira, 2025)
Economic development in a region is strongly influenced by the availability of adequate infrastructure. This study aims to examine the effects of road infrastructure, distributed clean water, and electricity consumption on the Gross Regional Domestic Product (GRDP) of Kupang City, both partially and simultaneously. The study uses secondary data from Statistics Indonesia (BPS) for Kupang City covering the period 2008–2022, including road length, the volume of distributed clean water, and electricity consumption. The analysis employs multiple linear regression (OLS) using EViews, complemented by classical assumption tests, hypothesis testing, and the coefficient of determination (R²). The results indicate that the three infrastructure variables jointly affect Kupang City’s GRDP, with an R² value of 61.93%. Partially, road infrastructure has a negative and significant effect on GRDP, distributed clean water has a positive but insignificant effect, and electricity consumption has a positive and significant effect. The policy implications emphasize the need to strengthen the reliability of electricity supply as a driver of economic activity, improve the effectiveness of road infrastructure spending by prioritizing segments that enhance production–market connectivity and adopting needs-based maintenance, and upgrade clean water services by expanding coverage and improving the quality and continuity of distribution so that its contribution to economic growth becomes more tangible.
Keywords: Road Infrastructure, Distributed Water, Electricity Usage and GRDP